Effect of Ethanol Vapor Treatment on the Growth of Alternaria alternata and Botrytis cinerea and Defense-Related Enzymes of Fungi-Inoculated Blueberry During Storage - Ji, Yaru; Hu, Wenzhong; Liao, Jia; Xiu, Zhilong; Jiang, Aili; Yang, Xiaozhe; Guan, Yuge; Feng, Ke; Saren, Gaowa (Frontiers in Microbiology, 2021)
The aim of the present study was to investigate the effects of ethanol vapor on the inhibition of Alternaria alternata and Botrytis cinerea in postharvest blueberry and the induction of defense-related enzymes (DREs) activities in fungi-inoculated blueberries stored at 0 ± 0.5 °C for 16 d. Results indicated that, ethanol vapor markedly inhibited the mycelial growth of Alternaria alternata and Botrytis cinerea in a dose-dependent manner, with inhibition rates of 9.1% (250 μL L-1), 36.4% (500 μL L-1), 5.5% (1000 μL L-1) on Alternaria alternata and 14.2% (250 μL L-1), 44.7% (500 μL L-1), 76.6% (1000 μL L-1) on Botrytis cinerea, respectively. Meanwhile, ethanol vapor also enhanced the activities of DREs in fungi-inoculated blueberries, including β-1,3-glucanase (GLU), chitinase (CHI), phenylalnine ammonialyase (PAL), peroxidase (POD) and polyphenol oxidase (PPO). In particular, 500 μL L-1 ethanol vapor increased the activities of DREs by 84.7% (GLU), 88.0% (CHI), 37.9% (PAL), 85.5% (POD), and 247.0% (PPO) in Alternaria alternata-inoculated blueberries and 103.8% (GLU), 271.1% (CHI), 41.1% (PAL), 148.3% (POD), 74.4% (PPO) in Botrytis cinerea-inoculated blueberries, respectively. But, the activities of PPO were decreased by 55.2% and 31.9% in 500 μL L-1 ethanol-treated blueberries inoculated with Alternaria alternata and Botrytis cinerea respectively, after 8 d of storage. Moreover, the surface structure and ultrastructure of 500 μL L-1 ethanol-treated blueberry fruit cells were more integrated than those of other treatments. The findings of the present study suggested that ethanol could be used as an activator of defense responses in blueberry against Alternaria and Botrytis rots, by activating DREs, having practical application value in the preservation of postharvest fruit and vegetables.